Analisis Periodisasi Latihan Kondisi Fisik Berdasarkan Keseimbangan Beban Latihan dan Recovery Pada Tahap Persiapan Umum, Persiapan Khusus, Pra Pertandingan dan Pertandingan pada Klub Bola Voli Kharisma - Muchamad Marcelino; Dede Rohmat Nurjaya (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study was to analyze the balance of training load and recovery at each stage of the Kharisma Bandung volleyball team's periodization, which includes the general preparation, special preparation, pre-match, and match stages. This study used a descriptive analytical approach with a case study method, where data were collected through a review of the periodization master plan document and interviews with the team's physical conditioning coach. The object of analysis was a training program consisting of 17 microcycles, with details of 5 microcycles in the general preparation stage, 7 microcycles in the special preparation stage, and 5 microcycles in the pre-match stage. Increases and decreases in training load were calculated using the formula for percentage changes in volume and intensity between microcycles. The results showed that there was a difference in the calculation of training volume between the author and the physical conditioning coach in the first to second microcycles in the general preparation stage of 1%. Furthermore, a more significant difference was found in the 17th microcycle, where the author recommended a volume of 50%, while the coach set a volume of 90% — a value considered too high and unable to accommodate the high intensity in the final microcycle of traditional periodization. Differences were also found in the rate of intensity increase, with the authors suggesting a 3% increase per microcycle, while the physical conditioning coach implemented a 6% increase per microcycle. The study concluded that the Kharisma Bandung volleyball team's periodization master plan did not fully reflect the principles of optimal load balance and recovery, particularly in the final phase of the training cycle. These findings recommend adjustments to the volume determination during peak microcycles and control of the rate of intensity increase to conform to traditional periodization principles that are measurable and safe for athletes. Keywords: Training Load, Overtraining, Training Periodization, Supercompensation Recovery